Netter's correlative imaging abdominal and pelvic anatomy - Torigian, Drew A.; Hammell, Mary Kitazono; Netter, Frank H.; Marzejon, Kristen Wienandt; Machado, Carlos A. G. (Elsevier Saunders, 2013)
Visualize normal anatomy of the abdomen and pelvis like never before with Netter's Correlative Imaging: Abdominal and Pelvic Anatomy. This outstanding radiology reference from Dr. Drew A. Torigian and Dr. Mary Kitazono Hammell features beautiful and instructive Netter paintings and illustrated cross-sections created in the Netter style, presented side by side with high-quality patient MR images to help you envision and review both gastrointestinal and genitourinary anatomy section by section